Penguatan Tata Kelola Pemerintahan Desa Mojosari melalui Implementasi Sistem Digital Pelayanan Administrasi Berbasis TIK - Dian Wijaya (MAJAPAHIT POLICY, 2025)
This study aimed to understand the role of the Mojosari Village website in improving the efficiency of village administrative services and as a concrete manifestation of the implementation of good governance based on information and communication technology. The village website serves not only as an information medium but also as a means of providing faster, more transparent, and more accountable public services, thereby meeting the public's demands for modern and efficient administrative services. This study utilized Francis Fukuyama's theory of good governance as an analytical framework. In this theory, in addition to the Rule of Law aspect, two main indicators are used: Capacity and Autonomy. Capacity is defined as the village government's ability to provide optimal services to the community, while autonomy relates to the village government's level of independence in managing technology-based administration and service systems. The research method used was descriptive qualitative. Data were obtained through direct observation of the use of the village website and in-depth interviews with administrators and community members as service users. This approach enabled the researcher to describe the phenomenon in more detail and comprehensively regarding the implementation of e-government at the village level. The results showed that the Mojosari Village website has been able to create efficiency and effectiveness in administrative services. The public can access information and administrative services more easily, quickly, and transparently. Thus, it can be concluded that Mojosari Village has successfully utilized information technology to achieve good governance in accordance with the principles of capacity and autonomy proposed by Fukuyama.